Diversity and Distribution of Predatory Insects in Non-outbreak and Post-outbreak Estates of an Oil Palm Plantation in Beluran District, Sabah, Malaysia: Hemipteran diversity in Beluran Estate, Sabah - MOHAMAD HARRIS NASIR; MUHAMMAD HAFIZ AIMAN; MOHANARAJ SITHAMPALANADANARAJAH; JOSHUA MATHEWS (Borneo Journal of Resource Science and Technology, 2023)
Hemipteran predator species from the families Reduviidae and Pentatomidae are a group of insects that play a crucial role as natural enemies of leaf-eating pests in oil palm plantations by maintaining the population of pests below the economic. The promotion of natural enemies can be an effective and sustainable approach to pest management. A census was conducted between June and August 2022 in nine plantations in Beluran district, Sabah to compare the species composition between recent leaf-eating pest in outbreaks and non-outbreak estates using sweep nets and active visual surveys. A total of 355 individuals from seven species of two different families were recorded, with Reduviidae being the most abundant family: Sycanus annulicornis, S. affinis, Cosmolestes picticeps, Velinus nigrigenu, Campsolomus nr. sp. (Hemiptera: Reduviidae), Platynopus melanoleucus and Eocanthecona furcellata (Hemiptera: Pentatomidae). The diversity indices of the predatory insects were significantly higher (p<0.01) in non-outbreak estates (H’ = 1.682, 1-D = 0.763) compared to post-outbreak estates (H’ = 1.344, 1-D = 0.683), which recorded a higher dominance value (D = 0.32) of a single species, leading to a decrease in the diversity indices. The Pentatomidae family was only found at non-outbreak estates, while the other Reduviidae species were highly abundant and distributed throughout all study locations. The S. annulicornis and S. affinis were only found on beneficial plants, while E. furcellata and P. melanoleucus were highly abundant within the oil palm planting area. These findings provide insights into the importance of maintaining the beneficial plant and reducing the impact of pest outbreaks on the diversity and abundance of predatory insects in oil palm plantations.